DAMPAK KENAIKAN HARGA JASA SEWA MOBIL TERHADAP OMSET PENDAPATAN RENTAL LANCAR JAYA TRANS SUKOREJO SITUBONDO - Hafid, Moh. (Al-Idarah, 2024)
In Sumberejo village, Banyuputih subdistrict, Situbondo regency, there are thirteen car rental service entrepreneurs who are exactly the same and operate in the transportation services sector, all of which provide and serve car rentals, tour packages, tours and travel, some even have additional drivers. Personally, from several services offered to consumers by all rental entrepreneurs in Sumberejo, there are differences regarding pricing, some provide cheap prices, and there are those who provide expensive prices, thus greatly affecting the income turnover of fellow rental entrepreneurs. The Sumberejo Situbondo Car Rental Association organization which is a combination of several car rentals in Sumberejo Village, which consists of entrepreneurs or rental owners, and the Drivers Association, in this association the main objective is to provide gatherings and coordination among rental entrepreneurs, how to regulate pricing matters. uniforms are not varied, carry out religious activities together, social activities, and other matters related to the transportation bureau. However, what has been agreed and stated in the deed of agreement between one entrepreneur and another rental entrepreneur is applied in the field in providing different pricing and continuing to use a cheaper approach, many consumers will be left behind and more expensive consumers will be left behind. This research uses qualitative field data analysis. The final conclusion from the research results is that price increases have a very positive effect on income turnover. Price differences have a very positive effect on income turnover.